Distal rectal skip segment Hirschsprung disease: Case report and review of literature. (3rd September 2019) - Shenoy, Archana; De Los Santos, Yanel; Johnson, Kevin Neil; Petroze, Robin
Abstract: Background: Lack of ganglion cells on adequate suction rectal biopsy is the gold standard for diagnosis of neonatal Hirschsprung disease (HD), and the presence of ganglion cells precludes such a diagnosis.Case report: A 10-day old male neonate presented with clinical symptoms concerning for HD. However, suction rectal biopsies demonstrated submucosal ganglion cells on the distal suction rectal biopsies (2 cm from anal verge) and not on the proximal (3 cm from anal verge), with similar findings on repeat biopsies. Clinical suspicion remained high, and diagnostic laparoscopy with intraoperative biopsies confirmed aganglionosis with a sigmoid transition. A pull through resection confirmed the diagnosis of distal rectal skip segment HD (SSHD) with a ∼6 cm length of circumferential aganglionosis extending into the proximal sigmoid.Conclusions: Discordant results on suction rectal biopsies should raise the possibility of SSHD. Awareness of the entity can facilitate timely definitive management in neonatal period.